Women on board: the impact on financial performance of companies listed on Bursa Malaysia - Ahmad, Maslina; Abdirahman, Sadik; Annuar, Hairul Azlan (University Malaya, 2024)
The current study aimed to investigate the link between women representation as board members and Bursa Malaysia-listed companies’ financial performance. The data collection utilised the Bursa Malaysia website to obtain the 100 leading public listed companies (PLCs). This research covered a period between 2016 and 2018. The association between the dependent and independent variables was evaluated using panel data regression analyses. The findings indicated that the representation of women directorial board members and the ways a company performed financially were negatively associated. Conversely, positive associations were found between women on audit committee and firm performance, and when women serve as CEOs or Chairmen of the boards. The study also found that women directors with accounting and finance background, their age, tenure, and independence have no significant association with firm performance. The main academic contribution this study makes is that evidence was discovered that women on boards was an influential factor after 2016; by this year, Malaysian listed companies were to have implemented this policy effectively. The results of the study showed that firms’ performance may be enhanced when women fill the positions as audit committees or CEOs or Chairmen. This may motivate listed firms in Malaysia to appoint more qualified women as members of the boards not only to adhere to the government policy, but also to gain benefits in term of financial performance. The study only examined the top 100 PLCs and this may affect the generalization of the results. Second, the research only covered the years 2016 to 2018, so the study might not fully illustrate the actual long-term impact that women directorial board members had on companies’ performance. Furthermore, this paper did not examine the critical mass of women directors in depth, although the amount of women board members needed to have a major effect will be determined by this.